2007
DOI: 10.1183/09031936.00061806
|View full text |Cite
|
Sign up to set email alerts
|

Serological test and chest computed tomography findings in patients withMycobacterium aviumcomplex lung disease

Abstract: The present authors have previously reported the usefulness of a serodiagnostic test to detect serum glycopeptidolipid (GPL) core antibody in diagnosingMycobacterium aviumcomplex (MAC) lung disease in immunocompetent patients. The aim of the present study was to investigate correlations between the levels of antibody against GPL core and chest computed tomography (CCT) findings in patients with MAC lung disease.A total of 47 patients with MAC-positive culture from their sputum and who had radiographic abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
3
17
2
Order By: Relevance
“…A weak positive correlation between the extent of MAC-PD on chest CT and antibody levels was observed (r50.24, p50.0309), as reported in previous studies [9,10]. This observation may indicate that the antibody levels reflect MAC disease activity.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A weak positive correlation between the extent of MAC-PD on chest CT and antibody levels was observed (r50.24, p50.0309), as reported in previous studies [9,10]. This observation may indicate that the antibody levels reflect MAC disease activity.…”
Section: Discussionsupporting
confidence: 66%
“…To assess the extent of disease, we divided the lung into 18 segments on a conventional chest CT, according to the anatomical segments, as in previous studies [9,10]. The extent of disease was expressed as the number of involved CT segments in which MAC lesions were present.…”
Section: Chest Computed Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…The disease type was determined on the basis of the HRCT results as previously described (6). The extent of the disease was defined based on the number of CT segments in which MAC lesions were present, as described previously (6,22).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies found a weak correlation between the GPL core antibody levels and the extent of the disease on chest computed tomography (CT) (9,22). In addition, the antibody levels were found to be decreased after surgical resection in patients with MAC pulmonary disease (21).…”
mentioning
confidence: 98%